IMPLEMENTASI GREEN HUMAN RESOURCE MANAGEMENT, EMPLOYEES GREEN BEHAVIOR DAN CORPORATE SOCIAL RESPONSIBILITY PADA PERUSAHAN INDUSTRI DI ACEH - Munawarah, Munawarah; Syaripuddin, Syaripuddin; Yumna, Munadya; Simahatie, Mai (FISIP Universitas Malikussaleh, 2025)
The aim of this research is to determine the level of understanding and sensitivity of companies towards the impact of industrial waste. The method used in this research is a qualitative method which prioritizes observing phenomena and exploring the essential meaning of phenomena. The research results show that Industrial Companies in Aceh have implemented Green Human Resource Management where Green HRM is the foundation that supports environmentally friendly behavior among employees, which in turn strengthens the company's CSR commitment. Industrial Companies in Aceh already understand the concept of Employees' Green Behavior where Employees' Green Behavior reflects the success of Green HRM and direct contribution to achieving CSR goals. Industrial Companies in Aceh have implemented corporate social responsibility. Green HRM and CSR support each other; Green HRM policies facilitate CSR implementation by ensuring that a company's HR practices support social and environmental sustainability goals.